Care for creation : a call for ecological conversion - Francis, Pope, 1936-; Vigini, Giuliano, 1946- (Maryknoll, New York : Orbis Books, 2016)
Pope Francis's historic encyclical Laudato Si' was not merely the first encyclical to address ecology and care for creation; it was the manifesto for a new humanism, an outline of the values and principles allowing us to live together in our common home. Drawing not only on that encyclical but on Pope Francis's extensive writings, speeches, and homilies, Care for Creation lays out his comprehensive vision of integral ecology. As Francis argues, concern for the earth is more than an ethical challenge--it calls for a profound conversion of values that involves a new understanding of our relation to God's Creation, both the Earth and its creatures, as well as our fellow human beings. (Publisher).
Care for creation -- Degrading our common home -- Ethical failure -- This economy kills -- The globalization of indifference -- Redefining progress -- The search for the common good -- Toward a culture of integral ecology -- Constructing the human city -- The spiritual dimension of life.
Translation of: Custodire il creato : proposte per una conversione ecologica.
Collection of some of Pope Francis' writings on the environment.
Keywords: Human ecology -- Religious aspects -- Catholic Church; Ecology -- Religious aspects -- Catholic Church; Environmental protection -- Religious aspects -- Catholic Church; Environmentalism -- Moral and ethical aspects; Environmental justice -- Religious aspects -- Catholic Church; Ecotheology